Embryonic development in the Patagonian red snail Odontocymbiola magellanica (Neogastropoda: Volutidae): morphology and biochemistry - Bigatti, Gregorio (2014)
Embryo morphology, feeding mechanism and changes in composition of the egg capsule content during development (intracapsular fluids and embryos) were studied in Odontocymbiola magellanica from newly spawned egg capsules to the pre-hatching juvenile stage. Changes in embryo morphology and behavior are presented, based on observations and micrographs of living specimens and scanning electron microscopy. The arrangement of velar cilia and athrocytes and shell gland location and development differed markedly from other studied caenogastropods. Embryo ingestion of intracapsular fluid was promoted by velar ciliary currents at least from the early veliger stage, while feeding by grazing on the inner membranous layer of the egg capsule was rarely observed until juveniles were about to hatch. The main growth of embryos occurred during the veliger stages. A significant nutritional investment in egg capsules, as compared with other South American volutids was observed. Nutrition from proteins seemed to predominate at the expense of a high molecular weight fraction (>220 kDa). Calcium concentration in the intracapsular fluid remained constant during development, but notably, the total intracapsular content (i.e., the amount contained in both fluid and embryos) increased 3-fold, which may be explained by extraction from the egg capsule magnesium-rich calcite cover, or alternatively, by uptake of calcium from the surrounding sea water. Ammonia, a major end-product of nitrogen metabolism in marine invertebrates, was present in both embryos and intracapsular fluid, from which it may easily diffuse to the surrounding sea water through the egg capsule wall. Our results on embryo morphology, development and biochemical changes provide useful comparative data for evolutionary and developmental studies in the Volutidae as well as in other caenogastropods.